Russian Northwest: An integral Assessment of the Conditions of Regional Social, Environmental and Economic Systems and Quality of Life - Dmitriev, Vasily; Kaledin, Nikolai (Baltic Region, 2017)
The article describes the results of an integral assessment of the regional social, environmental and economic systems (SEES) and the quality of life (QOL) in the regions of Russia’s Northwestern Federal District (NWFD). This work aims at giving an integrated assessment of SEES in the Arkhangelsk and Murmansk regions in comparison to the Moscow region. The authors examine the QOL in 10 NWFD regions, including the Baltic ones. The significance of the research work lies in an integrated and comprehensive assessment of the regional SEES and QOL in 2006, 2009, 2012, and 2013 in view of the effect of priorities within and between groups of assessment parameters. Another important result is the identification of ‘stability limits’, when regions retain their QOL whereas their regional environmental characteristics change. The proposed methodology is based on multi-criteria and integrated approaches, the aggregate index method, and the parameter analysis and synthesis. The assessment of SEES and QOL was performed for five classes (from ‘1 — high’ to ‘5 — poor’) based on calculating statistics for 3—6 groups of assessment criteria at two levels of convolution. The analysis of the data obtained shows an upward trend in QOL in the regions. The authors suggest assessing stability of SEES on the basis of critical values of aggregate indices, at which a given SEES maintain its characteristics and regime properties within a certain QOL class.